MENELISIK PERAN GURU DALAM MEMBANGUN KARAKTER: PERSPEKTIF FILSAFAT IDEALISME DI SEKOLAH DASAR - Atikah Nur Izzah; Ningsih, Tutut Hartina Ilmiah; Ade Eka Anggraini; Siti Mas’ula (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine the role of teachers in building student character in elementary schools, seen from the perspective of the philosophy of idealism. Character education is an integral part of the educational process which aims to form individuals with noble character. In the philosophy of idealism, character education does not only focus on aspects of the academic curriculum, but also on the formation of moral and ethical values that must be implemented by teachers as role models. This research used a qualitative descriptive method with interview and observation techniques with several teachers at MI Riyadlul Ulum, Pasuruan City. The research results show that the teacher's role in building character education is based on 4 approaches, namely exemplary, habitual, integrative and collaborative approaches. Overall, the idealist perspective in elementary school education emphasizes the importance of character education, the role of teachers as role models, effective educational management, and the integration of idealistic values in all aspects of learning.